Exploration of Public Health Students’ Remote Course Learning Experience and Mental Wellbeing during the COVID-19 Pandemic - Lennon, Chelsea (East Carolina University, 2021)
The COVID-19 pandemic has significantly impacted students’ learning experiences. While many universities have switched the in-person courses to online courses, few have taken the next steps to explore the effects on students academically and personally. The purpose of this study is to explore the implications of COVID-19 on Public Health undergraduate students at East Carolina University and explore the effects that these students may be experiencing on their remote course learning experience and personal wellbeing. Public Health students represent a key demographic in that they are training in the prevention and management of diseases such as COVID-19, and subsequently, experience a unique curriculum. In this study, the change in the students’ course delivery methods due to COVID-19 was assessed. Additionally, the impact on the students’ learning experiences and wellbeing due to the change in course delivery and COVID-19 learning was determined. Students completed a survey sharing their opinion and an optional, virtual semi-structured interview further. This study will help to uncover how Public Health students are being affected and how University resources can contribute to the students’ wellness and smooth transition from traditional campus courses to distance learning courses. It will also provide data to support infrastructure plans for students and faculty members to succeed in their academic learning during the pandemic.
Keywords: remote instruction, learning obstacles, learning experiences